PKM PENGRAJIN SABUT KELAPA DESA GINTUNG DALAM INOVASI BANTAL TERAPI HERBAL ARUMATIK (TERHARUM) - Fitriana, Rina; Murwonugroho, Wegig; Hartini, Hartini; Hartanti, Monica Dwi (Universitas Trisakti, 2025)
This Community Service Program uses the Community-Based Empowerment (CBM) scheme. The Mokla Coir coconut fiber craftsman group, which has been operating since 2019, faces various challenges in managing coconut fiber waste as the primary raw material. These challenges include the low market value of coconut fiber, a lack of innovative product diversification, and unsystematic production processes. Other problems are the risk of injury due to unsafe machine technology and limited marketing in traditional markets. This Community Service Program aims to develop an innovative product, the Aromatic Herbal Therapy Pillow (TERHARUM), with a higher market value. This coconut fiber-based product has the potential to be a healthier alternative to dacron and kapok. However, it must meet quality standards to reduce health risks such as allergies and sleep disorders. By utilizing the design thinking method (empathy, ideas, prototypes, and testing), the analysis highlights the need for more efficient production management, physical endurance testing, and comfort evaluation. The resulting pillow is designed to be innovative, high-value, safe, and comfortable for consumers. Overall, this Community Service Program has provided a solution for processing coconut fiber waste into high-value products, building a safe and comfortable production system, and expanding marketing reach to the international market.